A numerical investigation of air-cooled steam condenser performance under windy conditions - Owen, Michael Trevor Foxwell (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.